Konsep Kebebasan Manusia Menurut Baruch Spinoza dalam Perspektif Filsafat Politik - Yulianus Patrisius Firman (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
Discussions on human freedom in Spinoza’s philosophy are generally dominated by metaphysical and ethical interpretations, while its systematic relevance to political philosophy remains insufficiently explored. This paper addresses this gap by situating Spinoza’s concept of freedom within a political framework that connects rational self-determination with the structure of collective life. Employing a qualitative literature approach with analytical-philosophical methods, this study critically examines Spinoza’s primary works—Ethics, Theological-Political Treatise, and Political Treatise—alongside selected secondary sources. The analysis demonstrates that freedom, in Spinoza’s view, is constituted not by the absence of external constraints but by the capacity to act through adequate ideas grounded in reason. Such a conception redefines political freedom as the condition that enables individuals to participate rationally within a shared order. Furthermore, the findings indicate that democratic arrangements provide the most adequate space for the realization of rational freedom, as they facilitate participation, safeguard intellectual autonomy, and orient collective life toward common welfare. This paper contributes to political philosophy by clarifying the intrinsic relation between rational freedom and democratic order, while also offering a contextual reflection relevant to contemporary socio-political dynamics.